Implementasi Kerja Sama Universitas Al-Azhar dan UniMAP dalam Pengabdian Masyarakat melalui Diskusi Perluasan Hutan Mangrove - Nurdiana, Nurdiana; Siregar, Zufri Hasrudy; Nugraha, Yoga Tri; Suherman, Suherman; Nasution, Adinda Juwita; Rida, Rizkha; Irwanto, Muhammad; Bin Jusoh, Muzammil (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Partnerships between universities and partner institutions are strategic for study program accreditation and for implementing the Tri Dharma of Higher Education. In 2025, Al-Azhar University established an international collaboration with Universiti Malaysia Perlis (UniMAP) and the Village Forest Management Institution (LPHD) of Pasar Rawa, Langkat Regency, in the field of community service. The activities included a networking session, strategic discussions on converting palm oil plantations back into mangrove forests, and a joint mangrove planting action. This initiative aims to restore coastal ecosystems as habitats for marine life, such as fish, crabs, and shrimp. Through this synergy, it is expected that the motivation of the Pasar Rawa Village community, particularly the LPHD, will increase in managing and preserving the mangrove area sustainably for the welfare of the coastal ecosystem.